Drug solubility in fatty acids as a formulation design approach for lipid-based formulations: a technical note. (2nd September 2018) - Lee, Yung-Chi; Dalton, Chad; Regler, Brian; Harris, David
Abstract: Lipid-based drug delivery systems have been intensively investigated as a means of delivering poorly water-soluble drugs. Upon ingestion, the lipases in the gastrointestinal tract digest lipid ingredients, mainly triglycerides, within the formulation into monoglycerides and fatty acids. While numerous studies have addressed the solubility of drugs in triglycerides, comparatively few publications have addressed the solubility of drugs in fatty acids, which are the end product of digestion and responsible for the solubility of drug within mixed micelles. The objective of this investigation was to explore the solubility of a poorly water-soluble drug in fatty acids and raise the awareness of the importance of drug solubility in fatty acids. The model API (active pharmaceutical ingredient), a weak acid, is considered a BCS II compound with an aqueous solubility of 0.02 μg/mL and predicted partition coefficient >7. The solubility of API ranged from 120 mg/mL to over 1 g/mL in fatty acids with chain lengths across the range C18 to C6. Hydrogen bonding was found to be the main driver of the solubilization of API in fatty acids. The solubility of API was significantly reduced by water uptake in caprylic acid but not in oleic acid. This report demonstrates that solubility data generated in fatty acids can provide an indication of the solubility of the drug after lipid digestion. This report also highlights the importance of measuring the solubility of drugs in fatty acids in the course of lipid formulation development.